2022
DOI: 10.1149/1945-7111/ac609e
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Plasma Modified Carbons for PEMFC with Increased Interaction with Catalyst and Ionomer

Abstract: Vulcan XC72 carbon black, conventionally used as electrocatalyst support in proton exchange membrane fuel cells (PEMFCs), was doped with nitrogen functionalities by exposing it to nitrogen plasma, and the effect on its morphology, structure and texture and surface properties was investigated. In particular, the strength of the interaction between the modified carbon and Nafion® ionomer was evaluated by isothermal titration calorimetry, and an enhanced exothermic effect was observed on increasing the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Studies have shown that the carbon support with surface-modified carbons, which have N positively charged functional groups, reinforced the interaction of the supports with the negatively charged ionomer functional groups (−SO 3 − ). 31 This further realized better distribution of the ionomer on the support, hence a better proton accessibility, especially in lower humidity operation conditions. 32,33 We note that this effect has been demonstrated with pure Pt catalysts only, but at the present understanding, it should be transferable also to other catalysts, such as Pt alloys and shaped controlled catalysts.…”
Section: Introductionmentioning
confidence: 93%
“…Studies have shown that the carbon support with surface-modified carbons, which have N positively charged functional groups, reinforced the interaction of the supports with the negatively charged ionomer functional groups (−SO 3 − ). 31 This further realized better distribution of the ionomer on the support, hence a better proton accessibility, especially in lower humidity operation conditions. 32,33 We note that this effect has been demonstrated with pure Pt catalysts only, but at the present understanding, it should be transferable also to other catalysts, such as Pt alloys and shaped controlled catalysts.…”
Section: Introductionmentioning
confidence: 93%
“…The proton species present in the acid group are dissociated and become solvated when the membrane is hydrated. Inside the polymer, the solvated protons are free and produce electrolyte conductivity [20,[27][28][29][30]. PEMFCs are capable of having a power output of 1-300 kW with a high cost [17].…”
Section: Types Of Fcsmentioning
confidence: 99%
“…But, the main shortcoming behind the PEMFC commercialization is the usage of costly Pt catalysts and their scarcity in different geographical locations. Different methods for high utilization of Pt are employed, including alloying Pt with other transition metals, tuning the morphology and crystallite size, heteroatom doping, etc. Investigations show incorporation of less-expensive 3d group transition metals into Pt lattice advances the kinetics of the electrochemical processes involved. , The alloying of Pt with M (Fe, Co, Ni, etc.) shifts the d-band center of Pt from the Fermi level and thus decreases the Pt–Pt bond distance. , This change in the Pt–Pt bond length plays a significant role in ORR and HOR at the cathode and anode sides, respectively.…”
Section: Introductionmentioning
confidence: 99%